Usefulness of cocaine drops in investigating infant anisocoria. (November 2017) - Martin, Gilles C.; Aymard, Pierre-Antoine; Denier, Charlotte; Seghir, Caroline; Abitbol, Marc; Boddaert, Nathalie; Bremond-Gignac, Dominique; Robert, Matthieu P.
Abstract: Introduction: Whereas apraclonidine has eclipsed cocaine test in the exploration of unilateral miosis in adults, its use in infants is avoided because of the risk of central nervous system depression. This chart review evaluates the usefulness of cocaine drops in infants. Methods: Infants under the age of one referred for unilateral miosis between November 1, 2009 and November 1, 2015, were reviewed. Patients underwent the following protocol: (1) in case of isolated miosis, cocaine test was performed. If the miotic pupil did not dilate, imaging was performed. Dilation in both eyes led to simple clinical follow-up. (2) In case of miosis associated with ptosis or iris heterochromia, imaging of the brain, neck and chest was directly performed. Results: Twenty-six children were included. Twenty-two presented an isolated miosis; three had ipsilateral ptosis, and one had no pupillary light reflex in the miotic eye. Cocaine tests performed in the 22 patients led to imaging in four, which was always normal. No side effect of the test was noticed. Imaging found one neuroblastoma and one intraorbital hemolymphangioma in two patients presenting miosis plus another sign. Imaging was avoided for 18 patients thanks to negative cocaine test. Discussion: Urgent imaging is mandatory in infants presenting with miosis associated with other localizing sign on the sympathetic nerve pathway (Horner syndrome). Since the uselessness of complementary investigations in isolated infantile miosis cannot be proven so far, cocaine test remains the gold standard, as it is safe, cheaper and less stressful than systematic imaging. Highlights: New refractometers have increased the number of infants referred for anisocoria. Systematic imaging should be avoided in case of purely isolated miosis. Cocaine test remains useful to exclude Horner syndrome and avoid unnecessary imaging.